Pengaruh Harga dan E-WOM Electronic Word Of Mouth Melalui Media Sosial TikTok Terhadap Minat Beli Produk Skincare Skintific - Indira Safitri; Natal Indra (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This study aims to find out how much price and E-WOM (Electronic Word of Mouth) influence through TikTok social media on the buying interest of Skintific skincare products. This study uses a quantitative method with the population of skincare users in the area around the research conducted. The sample was taken using the Lemeshow formula, so that the number of samples obtained by 100 respondents with the purposive sampling technique used three criteria collected through a questionnaire in the Likert scale unit. Data processing uses SPSS version 26 software for data quality tests, classical assumption tests, multiple linear regression analysis, hypothesis tests, and determination coefficient tests. The results of the study show that price and E-WOM (electronic word of mouth) through TikTok social media have a positive and significant effect on the buying interest of Skintific skincare products both partially and simultaneously.